Comprehensive Midwifery Care for Mrs. F Through Continuity of Care: Asuhan Kebidanan Komprehensif untuk Ny. F Melalui Kesinambungan Asuhan - Dewi, Wistri Cendra Mulya; Hanum, Sri Mukhodim Faridah (Indonesian Journal on Health Science and Medicine, 2025)
Introduction Comprehensive midwifery care includes pregnancy, childbirth, postpartum, newborns, and family planning (KB). The aim is to reduce the maternal mortality rate (MMR) in Indonesia through Continuity of Care (COC). This research method uses a descriptive method with case studies, collecting data through interviews, observation, physical examination and documentation. The data was analyzed for midwifery care using the SOAP technique. The results of the mother experiencing back pain during pregnancy were overcome with prenatal yoga. The delivery went normally without complications, the baby was born spontaneously weighing 3,200 grams and an Apgar score of 8-9. In the postpartum period, the mother complained of perineal wound pain and with early ambulation the pain was reduced. When the mother has finished postpartum, she is ready to become an IUD birth control acceptor. The conclusion was that no problems or abnormalities were found, so Mrs. F is categorized as normal/physiological. Highlights: Full cycle midwifery care applied from pregnancy to family planning. Non-pharmacological methods like prenatal yoga proved effective. Case supports COC as a model for safe, physiological maternal care. Keywords: Continuity of Care, Midwifery Care, Comprehensive